FORECASTING TECHNIQUES OF CONTACT HERBICIDE SALES USING SINGLE MOVING AVARAGE METHOD IN UD. LUMBUNG TANI - Umairoh; Rizaldi; Hommy Dorthy Ellyany Sinaga (Informatika, Universitas Jenderal Soedirman, 2022)
The process of supplying or stocking fertilizers at UD. Lumbung Tani is still carried out manually or only based on previous sales estimates, resulting in excess and shortage of contact herbicide stocks. The purpose of this study was to determine the amount of inventory derived from previous contact herbicide sales data using the SMA method to predict the contact herbicides gramoxone, tamaxone, paratop, himaquat, naraxone with a smaller error rate. The results showed that the MAPE SMA3 values ​​for each type of herbicide were 22. 13%, 22.35%, 22.72%, 21.83%, 18.20%. Forecasting applications with Single Moving Average can determine the prediction of contact herbicide supplies in the next period. By using the SMA3 method the owner of UD. Lumbung Tani can forecast sales in the following month which is more efficient and effective.